PENGARUH SUHU DAN KELEMBAPAN TERHADAP NILAI SETTING TIME PADA SEMEN PCC (PORTLAND COMPOSITE CEMENT) DAN OPC (ORDINARY PORTLAND CEMENT) - Azra Nazirah Nafiah; Legasari, Leni; Anaser, Novadri; Safaruddin, Safaruddin (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Temperature and humidity are important factors in the drying and hardening process of semen. The temperature in the hardening process ranges from 10°C to 35°C with a relative humidity of 40% to 60%. This research aims to analyze the effect of temperature and humidity on the initial and final setting time values ??of OPC and PCC cement in five different environmental conditions. The research results show that the higher the humidity level, the longer it takes for cement to harden, both for PCC and OPC. Conversely, the lower the humidity, the faster the setting time occurs. In increasing the initial setting time, PCC cement showed an increase of 38.5%, while OPC cement was 37.5%. For the final setting time, cement OPC experienced a more significant increase of 41.65%, compared to PCC which was only 25%. This shows that OPC cement has a faster final setting time and is relatively less influenced by temperature and humidity than PCC. This study concluded that temperature and humidity significantly influence the setting time of cement, with different effects varying between OPC and PCC cements.